KARAKTERISTIK HIDRAULIK FILTRASI DAN CUCIBALIK FILTER BETON - , BUDI KAMULYAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Sand filter is a water purification apparatus that has been widely used in Indonesia. It effectively removes the suspension particle and produces clean water. The use of sand filter frequently faces the problems, such as decreasing capacity of clean water production due to surface clogging caused by sand particle stratification after the backwashing process, decreasing filter capability to purify water due to dirty filter resulted from the velocity and the time of backwashing, which are too low and too short, respectively. Sand filter backwashing is restricted by the velocity and pressure to avoid the sand particle from being transported out of the filter. Such restriction causes a longer time of backwashing process and the need for energy/electricity to generate the backwashing pump as well as to provide washing water. To cope with the above-mentioned problems, porous concrete media (concrete filter) is studied and proposed as an alternative to substitute the sand filter. The objective of this research is to study the characteristics of filtration hydraulic and concrete filter backwashing, including the following aspects : 1) the changing of particle diameter and porosity of concrete filter due to the additional cement as the sand binding substance